Microbial metabolites control self-renewal and precancerous progression of human cervical stem cells - Jihyeon Myeong; Minho Lee; Bawool Lee; Joon Hyung Kim; Yeji Nam; Yeseul Choi; Jeongmin Kim; Se Young Jeon; Haewon Shim; Da-Ryung Jung; Youngjin Shin; Minsoo Jeong; et al. (Nature Communications)
Abstract Cervical cancer is the fourth most common female cancer, with the uterine ectocervix being the most commonly affected site. However, cervical stem cells, their differentiation, and their regulation remain poorly understood. Here, we report the isolation of a population enriched for human cervical stem cells and their regulatory mechanisms. Using single-cell RNA sequencing, we characterize the cellular heterogeneity of the human ectocervix and identify cluster-specific cell surface markers. By establishing normal and precancerous cervical organoids and an intralingual transplantation system, we show that ITGB4 and CD24 enable enrichment of human and murine ectocervical stem cells. We discover that Lactobacilli-derived lactic acid regulates cervical stem cells’ self-renewal and early tumorigenesis through the PI3K-AKT pathway and YAP1. Finally, we show that D-lactic acid suppresses growth of normal and precancerous organoids, while L-lactic acid does not. Our findings reveal roles of human cervical stem cells and microbial metabolites in cervical health and diseases.